Addisons Disease, Idiopathic Intracranial Hypertension and Empty Sella - In a 40-Year-Old Woman (Journal of Bangladesh College of Physicians and Surgeons, 2012)
A 40-year-old woman having normal menstrual history got  admitted into Bangabandhu Sheikh Mujib Medical  University (BSMMU) because of vomiting for previous two  months, with a background history of irregular steroid  intake for her bodyache for about six years. She was gaining  weight and gradually losing vision in her right eye and  noticed increased body pigmentation. Physical examination  revealed BMI 29 kg/m2, generalized pigmentation more  marked in palmar crease and oral mucosa, secondary optic  atrophy in right eye and papilloedema in left eye. After  biochemical and radiological investigation she was  diagnosed as a case of Addisons disease with idiopathic  intracranial hypertension (IIH) with empty sella   DOI: http://dx.doi.org/10.3329/jbcps.v30i1.11368   J Bangladesh Coll Phys Surg 2012; 30: 53-55